A QUALITATIVE ANALYSIS OF PRODUCT INNOVATION IN JORDAN’S PHARMACEUTICAL SECTOR - Ahmad Mowafaq Ghannajeh; Mohammad AlShurideh; Zu'bi M. F. Al-Zu'bi; Abdullah Abuhamad; Ghaleb Abu Rumman; Taghrid Suifan; Abdel Hakim O. Akhorshaideh (European Scientific Journal, ESJ, 2015)
Product Innovation, especially New Product Development (NPD) is critical for the continued success, development, and long-term growth of a company. Despite extensive research on how to achieve NPD success, NPD process remains a difficult and a highly risky venture. The research was conducted to investigate factors that affect NPD in the Jordanian pharmaceutical sector. Five factors were conceptually identified from past literature as initial factors. They include senior management support (SMS), cross-functional teams (CFT), customer involvement (CI), supplier integration (SI), and time to market (TTM). These five factors were used to build the basic research model as independent variables; whereas NPD was the dependent variable for the research model. A qualitative research methodology was designed and used to achieve the research objectives. The needed data for this study was captured through personal interviews, and a survey that targeted all Jordanian pharmaceutical companies. The population from which respondents was chosen included research and development managers, marketing managers, and other personnel involved in NPD process in Jordanian pharmaceutical producing companies. Through conducting a number of personal interviews and using Content Analytical Technique (CAT) for data analysis, the results of the research show the existence of a number of factors that affect NPD process in Jordanian pharmaceutical sector such as: SMS, TTM, CFT, R&R, Knowledge, and Technology. In addition, a number of factors were identified as NPD challenges and constraints. These factors include the toughness and lack of clarity in R&R related to NPD process, the lack of financial and human resources, as well as addition to increasing DC. This paper suggests several recommendations. Firstly, senior managements need to provide enough support to NPD process whether as financial, moral or any other kind of support. Secondly, companies have to take the necessary actions to speed up NPD process in order to get the benefits of introducing products earlier into the market. Thirdly, companies have to work hard to ensure higher levels of knowledge among their staff, especially those who are involved in NPD process by providing continued periodic training to them.